THE IMPACT OF NON-CARDIAC DISEASES ON THE COURSE AND PROGNOSIS OF LIFEPATIENTS WITH CHRONIC HEART FAILURE - Shukurov, R.T.; Abdullaev, T.A.; Kurbanov, R.D. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the effect of comorbidity on the frequency of decompensation and the prognosis of life of patients with CHF. Materials and Methods: The study involved 216 patients (136 men and 80 women, mean age 58.8±12.7 years) CHF, follow-up period of 12 months. The analysis of the development of adverse events, the number and duration of repeated hospitalizations of patients with CHF was conducted. Results: The most frequent component in the structure of comorbidity in patients with CHF is type 2 diabetes, which is observed in 27.8% of patients. During 1 year of observation, 1 (1.4%) patient with moderately severe comorbidity and 3 (3.4%) patients with high comorbidity died. Depending on the level of comorbidity, it was found that in patients with CHF with high comorbidity, the number of repeated hospitalizations during the year is higher than in patients with moderately severe and low comorbidity. Conclusions: The presence of comorbidity leads to an increase in adverse events, the number and duration of hospitalization of patients with CHF.